Analisis Penerapan Model Picture and Picture Terhadap Keterampilan Menulis Karangan Deskripsi di Sekolah Dasar - Azzahra, Hapsah; Endah Sugiharti , Rini; Rasis Najwan, Mohammad (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This article explores the challenges faced by elementary school students in writing descriptive essays. Previous research has identified several issues, including difficulties in understanding the topic, selecting appropriate opening words due to their abstract nature, linking sentences cohesively, adhering to the no guidelines of PUEBI (the Indonesian standard for writing), effectively conveying ideas, and a monotonous learning experience that lacks engaging instructional models. An analysis of various studies suggests that the